PERAN AUDIT OPERASIONAL DALAM MENILAI KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH - Fitriani, Anita; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The implementation of the operational audit in assessing service quality to the customer satisfaction and this research of the phenomenon which have been experienced by the subjects. The data collection technique has been performedby using observation, interviews and the documentation of internal data of the company. The result shows that the operational audit on the performance appraisal to the service function to assess the effectiveness and the efficiency of PT. Prusolid Citra Mandiri to comprehend the role of operational audit in assessing service quality to the customer satisfaction and analyzing matters that can improve the performance ofservice function to the customer satisfaction. In improving the service quality and the effectiveness and the efficiency service at PT. Prusolid Citra Mandiri in accordance with the standard procedure of service at PT. -Prusolid Citra Mandiri. It is expected from the research that has been carried outthat the management of the company is able to analyze and to makesome decisions to the improvement directionso operational audit of service function can be used as the control instrument on the division of insurance service so the effectiveness and the efficency of service function can be achieved.Keywords: Role of the operational audit, service quality, customer satisfaction